The impact of Special Allocation Fund (DAK) for health on achievements of health development performance in Indonesia - Agnes Putri Apriliani; Khoirunurrofik Khoirunurrofik (Economies, 2020)
In the implementation of decentralization, the Special Allocation Fund (DAK) for health is given to certain areas of Indonesia to support health financing. The performance of this financing, along with national health development priorities' achievements, is illustrated through the indicators of coverage of deliveries in health care facilities (PF) and coverage of first neonatal visits (KN1). Yearly increases in the health DAK budget have not been accompanied by increases in these coverages, and there are still significant disparities between regions. Using secondary data at the district/city level for 2014-2017, this study aims to investigate the impact of health DAK on coverage of PF and KN1. The analytical method deployed is linear regression of panel data using a fixed-effects model. The results show that in the short term, health DAK has a positive but insignificant effect on PF and KN1 coverage. However, health DAK has a positive and significant impact on PF coverage in the second year. Impact on KN1 coverage is unfeasible, even over a period of two years. These results indicate that the processes of planning, budgeting, and administering of health DAK require improvement so that benefits can be felt in the short term through better innovations in health programs. Nevertheless, given that our findings are based on a short period of study, the results from such analyses should consequently be treated with the utmost caution Therefore, future research should target a longer period of data collection to detect more trusty lagged effects and structural breaks of a policy intervention.
Keywords: E63; I15; I18; 330; decentralization; special allocation fund; health; health care facilities; coverage of first neonatal visits; Indonesia